Isolation of large bacterial plasmids and characterization of the P2 incompatibility group plasmids pMG1 and pMG5. - Hansen, J B (1978)
Large plasmids from Agrobacterium tumefaciens, Salmonella typhimurium, Escherichia coli, Pseudomonas putida, and Pseudomonas aeruginosa were routinely and consistently isolated using a procedure which does not require ultracentrifugation but includes steps designed to separate large-plasmid DNA from the bacterial folded chromosome. It also selectively removes fragments of broken chromosome. A variety of large plasmids was readily visualized with agarose gel electorphoresis, including five between 70 and 85 megadaltons (Mdal) in size, six between 90 and 143 Mdal, one that was larger than 200 Mdal, and one that was larger than 300 Mdal. This isolation procedure allowed initial estimation of the molecular sizes of the two IncP2 plasmids, pMG1 and pMG5, which were 312 and 280 Mdal, respectively. A standard curve for size determination by gel electrophoresis including plasmids between 23 and 143 Mdal in size did not extrapolate linearly for plasmids of the 300-Mdal size range. Unique response of different plasmids to the isolation procedure included sensitivity of IncP1 plasmids to high pH and the co-isolation of a 20-Mdal "cryptic" plasmid in conjunction.